"Empowered Voices: A Comparative Study of Female Identity in Manju Kapur's Works" (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Manju Kapur's novels offer a nuanced portrayal of contemporary Indian society, delving into the complexities surrounding autonomy, female identity, and self-determination. This paper examines the theme of women's quest for autonomy, tracing the journeys of female protagonists in Kapur's novels, including A Married Woman, Difficult Daughters, and The Immigrant. Despite being set against diverse social backdrops, these protagonists share a common aspiration for freedom and independence.